(3GdOjHGL GdePgH aj eYQag YdeGA CYjGf GdePgHs - (3EHQGgje Hf Ydj Hf eMeO, GHf aQMhf, HQgGf GdOjf GdjYeQj J (B799 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGQF GdfSje eHjO GdCee s
(3BNQgG (B:s
(3bGd eDdag (B: (3hcGf GdaQGZ ef JCdjaI ai TgQ TYHGf ef TghQ SfI (B761(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B176 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B150 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg Ndjd GdNGdOi HGdbOS s
Keywords: (3GdJGQjNs